The Patriarchy Index for Asia: A new tool for subnational analysis of gender inequalities - Mikołaj Szołtysek; Bartosz Ogórek; Mateusz Grzyb; Siegfried Gruber (PLoS ONE, 2026)
Gender inequality remains a persistent barrier to development in many parts of Asia, yet the domestic foundations of this inequality—particularly within family systems—are often neglected in global measurement tools. This study introduces the Patriarchy Index (PI), a new metric constructed from census microdata to capture gendered power hierarchies in families across 22 Asian (including Egypt, treated here as part of the classical Asian patriarchal belt) countries and 652 subnational administrative units. Of particular interest to development practitioners and scholars, the PI offers a scalable, low-cost tool for subnational diagnostics, especially where standard measures of gender equality are missing or fail to reflect private-sphere constraints on women’s autonomy. Our study addresses whether domestic arrangements—such as patterns of co-residence, marriage timing, and age-based authority—can reliably capture institutionalized patriarchy, and what regional variation these patterns reveal. Using harmonized IPUMS-International census microdata and eleven theoretically grounded indicators, we construct a multidimensional composite index empirically validated through convergence with existing gender measures, divergence from unrelated metrics, and correlation with gendered development outcomes. Our study finds that family-based patriarchy is spatially clustered and highly variable at the subnational level. It further shows that higher PI values are significantly associated with reduced relative female labor force participation, even after controlling for structural variables such as gross national income and urbanization. These results underscore the PI’s value as a complementary measure: it captures dimensions of gender inequality that remain invisible to public-facing or outcome-based indicators and helps bridge the gap between domestic constraints and broader patterns of disenfranchisement. In contexts where legal reform and female empowerment are pursued without addressing household-level structures, the PI offers a diagnostic that speaks directly to the architecture of family systems—illuminating where and how deeper constraints on gender equality endure.